2022
DOI: 10.3389/fphar.2021.811719
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha -308G/A Gene Polymorphisms Combined with Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratio Predicts the Efficacy and Safety of Anti-TNF-α Therapy in Patients with Ankylosing Spondylitis, Rheumatoid Arthritis, and Psoriasis Arthritis

Abstract: Background: TNF-α has been reported to be closely associated with autoimmune inflammatory diseases. This study aims to investigate the role of TNF-α -308(rs1800629) G/A gene polymorphisms as well as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in predicting the efficacy and safety of TNF inhibitors (TNFi) in patients with ankylosing spondylitis (AS), rheumatoid arthritis (RA), and psoriasis arthritis (PsA).Methods: A total of 515 subjects (181 AS, 144 RA, 48 PsA, 10 hyperbilirubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Nevertheless, the field of allergic diseases had few Frontiers in Genetics frontiersin.org corresponding reports. TaqMan-MGB qPCR offered a reliable and affordable method for investigating SNPs with allergy disorders (Wang et al, 2021;Jin et al, 2022;Wang et al, 2022). Using this technology, we initially discovered that patients with allergic cough had a different distribution of the PAI-1 rs1799762 gene than healthy people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the field of allergic diseases had few Frontiers in Genetics frontiersin.org corresponding reports. TaqMan-MGB qPCR offered a reliable and affordable method for investigating SNPs with allergy disorders (Wang et al, 2021;Jin et al, 2022;Wang et al, 2022). Using this technology, we initially discovered that patients with allergic cough had a different distribution of the PAI-1 rs1799762 gene than healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Applied Biosystems methodology, genotyping was accomplished by TaqMan chemistry utilizing the real-time Prism 3730XL Sequence Detection System (ABI Inc. CA, United States). In our prior research, we have demonstrated the effectiveness of the TaqMan-MGB qPCR kit for the detection of gene polymorphisms (Wang et al, 2021;Jin et al, 2022;Wang et al, 2022). The Kappa test was used to examine the agreement between DNA sequencing and TaqMan-MGB qPCR, with a Kappa value of 1 and a p-value <.001.…”
Section: Taqman-mgb Qpcr Methodsmentioning
confidence: 99%
“…Recurrence of VTE was defined as: [1] dissemination of thrombus to new veins or venous segments; [2] formation of new thrombus at a different site; [3] new PE [23]. Hyperbilirubinemia (HB) and hyperlipidemia (HLP) were diagnosed by combining clinical symptoms and laboratory results as described in the previous publication [8]. In addition to this, apparently healthy individuals with no family history of coagulation disorders, no malignancies, rheumatic or chronic diseases and no abnormal laboratory test results were selected as healthy controls (HC).…”
Section: Subjectsmentioning
confidence: 99%
“…Given the crucial role of genetic factors in disease pathogenesis, single nucleotide polymorphisms (SNPs) have become a hot topic of research at present. In previous study, we reported the potential value of combining tumor necrosis factor-α (TNF-α) -308G/A gene polymorphism with neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in predicting the efficacy and safety of anti-TNF-α therapy [8]. Some inherited polymorphisms have been identified as high-risk factors for VTE, such as 4G or 5G polymorphism of plasminogen activator inhibitor 1 (PAI-1), G1691A mutation in the F5 gene (Factor V Leiden (FVL)), G20210A of the F2 (prothrombin) gene, and C677T of the methylenetetrahydrofolate reductase (MTHFR) gene.…”
Section: Introductionmentioning
confidence: 99%
“… 8 In addition to this, SNPs have also been shown to be closely related to drug responsiveness and the safety of therapy. 9 On this basis, it would be beneficial to analyze the variations in genetic susceptibility and clinical features of individuals carrying different genotypes to better understand the role of SNPs in the pathogenesis of disease.…”
Section: Introductionmentioning
confidence: 99%